Portfolio Inflows Eclipsing Banking Inflows : Alternative Facts? - Cerutti, Eugenio (IMF Working Papers; Working Paper ;, 2018)
Superficial examination of aggregate gross cross-border capital inflow data suggests that there was no substitution between portfolio inflows and bank loans in recent years. However, our novel analysis of disaggregate inflows (both by types of instrument and borrower) shows interesting heterogeneity. There has been substitution of bank loans for portfolio debt securities not only in the case of corporate and sovereign borrowers in advanced countries, but also sovereign borrowers in emerging countries. In the case of corporate borrowers in emerging markets, the relationship corresponds to complementarity across types of gross capital inflows, especially during periods of positive capital gross inflows after the global financial crisis. A large part of these patterns does not seem to be driven by a common phenomenon across countries associated with the global financial cycle, but rather by country-specific factors.